THE MEASURMENT OF URANIUM CONCENTRATION INDEFFERENT (13) TYPES OF NATURAL HERB. - Nasser Allah, Zainab (Iraqi Journal of Science, 2024)
In this research the uranium concentrations in (13) different types of natural herbsamples had been measured, and to limit the level of contamination with radionuclides. The determination of uranium concentration in these samples has beendone by using CR-39 track detector, the nuclear reaction used a source of nuclearfission fragments is 235U (n,f) obtained by the bombardment of 235U with thermalneutrons from (Am-Be) neutron source which has a flux of (5000 n cm-2 s-1). Theresults obtained show that the concentration of Uranium were calculated bycomparison with standard samples, and varies from 0.235 ppm in (calum) type to0.552 ppm in (Lazmender) type, all the results obtained are within the internationallevels as given by UNSCAR (United Nations Scientific Committee on the Effect ofAtomic Radiation) data.